The Effect Of Compensation And Work Motivation On Member Performance At The Mobile Brigade Corps Command Headquarters - Radityo Yusuf Al Giffari; Kemal Taufik; Suhardi Suhardi (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze and explain the effect of compensation on member performance, the effect of work motivation on member performance, and the simultaneous effect of compensation and work motivation on the performance of members of the Mobile Brigade Corps Command Headquarters. This study uses a quantitative approach, namely a method that processes data in the form of numbers to examine the relationship between variables objectively and measurably. However, this study is also strengthened by qualitative data in the form of statements, questionnaire responses, and interview results that help enrich the interpretation of the data. The study population was all 132 members of the Mobile Brigade Corps Command Headquarters, with 99 respondents selected through a sampling technique tailored to the research needs. Data analysis was carried out using Structural Equation Modeling–Partial Least Square (SEM–PLS) software version 4.0 which is capable of testing the model comprehensively, both partially and simultaneously. The results of the hypothesis test indicate that the compensation variable (X1) has a positive and significant effect on member performance (Y), and the work motivation variable (X2) is proven to have a positive and significant effect on improving member performance. Simultaneously, both independent variables also show a strong influence on member performance. The R-Square value of 0.435, or 43.5%, indicates that employee performance is influenced by compensation and work motivation, while the remaining 56.5% is influenced by other factors not included in this study. This finding underscores the importance of effective compensation policies and well-managed work motivation to improve overall organizational performance